Users Acceptance Model Adapting Sustainability-Oriented Modularity Methods Of Replaceable Filter Mask (Rfm) In Jinshan District, China - Xu, Yang (2024)
This research explores modular and sustainable design, focusing on developing of sustainable modular product design (mspd) to promote environmental protection. With the replaceable filter mask (rfm) as a case study, it examines user behavioral intentions by applying the theory of planned behavior (tpb) and the technology acceptance model (tam). After a comparative analysis of various models (tpb, tam, utaut, utaut2), the study concludes that the unified theory of acceptance and use of technology 2 (utaut2) is most suitable for assessing mspd as a new technology. A mixed-method sequential explanatory design was employed. In the quantitative phase, data from 500 mechanical industry employees (mies) in shanghai's jinshan district were analyzed using structural equation modeling (sem) to explore the willingness to use mspd-based rfm. The study also examined mediating and moderating effects through a chained structural model. In the qualitative phase, thematic analysis of structured and semi-structured interviews with mies provided insights into the factors influencing their willingness to use the rfm. Key findings indicate that latent variables in utaut2, such as performance expectancy, social influence, hedonic motivation, and habit, positively affect mies' use of mspd’s rfm. Newly added variables like decorativeness and innovativeness also play a significant role.